Disruptive information exchange requirements in construction projects: perception and response patterns. Issue 2 (17th February 2021) - Abdirad, Hamid; Dossick, Carrie S.; Johnson, Brian R.; Migliaccio, Giovanni
ABSTRACT: The current proliferation of custom information exchange initiatives in projects disrupts information exchange routines of design and construction firms. This paper investigates how firms perceive, interpret, and act upon information exchange requirements that do not align with their existing routines. This case study examines a construction project for which the owner specified highly custom requirements for digital production and delivery of project submittals. Using ethnographic methods, the project parties' existing routines and their patterns of perceiving and responding to the requirements were identified. These patterns showed that the parties perceived disruptions to the existing dispositions and rules that guided their routines and shaped their performance across projects. The project parties used a combination of deductive, inductive, and abductive reasoning mechanisms to interpret the requirements, expose the inefficiencies associated with their workflows, and set new ground rules for action. The grounded propositions in this study hold that the limited opportunities for inductive reasoning and reflective assessment of workflows in projects can press project parties into identifying alternative workflows through cognitive search and abductive reasoning. This, in turn, results in highly situated, temporary, and fragmented workflows that are not durable and effective to contribute to refinement of existing information exchange routines.